IMPLEMENTASI LOAD BALANCING DAN LINK REDUNDANCY NETWORK DENGAN 2 ISP MENGGUNAKAN ROUTING DI MIKROTIK ROUTER - Andreas Perdana; Adi Wibowo (Sienna, 2022)
The Internet, and in particular the World Wide Web, is widely used by businesses, government agencies, corporations and individuals. Based on that fact internet service providers offer a lot of choices, and it can be confusing so we end up choosing the expensive one just to make sure we get the speed we need. All internet service providers must have interference, be it caused by the weather or broken cables and so on. The load balancing method can be used to send and receive internet access on a network through several gateways. When we subscribe to an internet connection with 2 ISPs load balancing can be used as a bandwidth balancer. The principles of load balancing remain the same in any environment, although circumstances and applications will differ. Internet service providers use a balancing strategy to handle fluctuating amounts of incoming internet traffic. Load balancing effectively minimizes server response time and maximizes throughput. The role of load balancing is sometimes likened to that of a traffic police, as it is meant to systematically direct requests to the right location at a given moment, thereby preventing costly congestion and unforeseen incidents. The load balancer must ultimately provide the performance and security needed to sustain complex IT environments, and the complex workflows that occur within them.